Effect of walking speed on the gait of king penguins: An accelerometric approach. (21st December 2015) - Willener, Astrid S.T.; Handrich, Yves; Halsey, Lewis G.; Strike, Siobhán
Abstract: Little is known about non-human bipedal gaits. This is probably due to the fact that most large animals are quadrupedal and that non-human bipedal animals are mostly birds, whose primary form of locomotion is flight. Very little research has been conducted on penguin pedestrian locomotion with the focus instead on their associated high energy expenditure. In animals, tri-axial accelerometers are frequently used to estimate physiological energy cost, as well as to define the behaviour pattern of a species, or the kinematics of swimming. In this study, we showed how an accelerometer-based technique could be used to determine the biomechanical characteristics of pedestrian locomotion. Eight king penguins, which represent the only family of birds to have an upright bipedal gait, were trained to walk on a treadmill. The trunk tri-axial accelerations were recorded while the bird was walking at four different speeds (1.0, 1.2, 1.4 and 1.6 km/h), enabling the amplitude of dynamic body acceleration along the three axes (amplitude of DBA x, DBA y and DBA z ), stride frequency, waddling and leaning amplitude, as well as the leaning angle to be defined. The magnitude of the measured variables showed a significant increase with increasing speed, apart from the backwards angle of lean, which decreased with increasing speed. The variability of the measured variables also showed a significant increase with speed apart from the DBA z amplitude, the waddling amplitude, and the leaning angle, where no significant effect of the walking speed was found. This paper is the first approach to describe 3D biomechanics with an accelerometer on wild animals, demonstrating the potential of this technique. Highlights: We measured the gait of walking king penguins with an accelerometer. We described the change of the triaxial accelerations and the position of the body with an increasing speed. We discuss the value of accelerometry to describe the biomechanics of a walking animal.